Interatividade na TV digital: um estudo a partir da teoria do meio sobre impactos comunicacionais no telespectador - Faria, Watson Odilon Pereira de (2016)
The purpose of this dissertation is to review and complement the tests performed by UFPA, USP and UCB interactive digital TV Healthcare application developed for the Global ITV project to see if verify if this technological innovation, which is the interactive digital TV, is configured as an extension of man. Therefore, we supported in theory and study of applied methods of the new technology incorporated in the digital TV in Brazil that offers interactive services. As corpus of our study we explored the Global ITV project, and more specifically the interactive application that was developed by the team of the Catholic University of Brasilia in which this author participated actively. The methodological approach included tests at UCB and the other two institutions data measurement. The assumptions that guided the reflections followed the light of the contributions of McLuhan, Meyrowitz and Kerckhove, who organized and continued the studies of this theory.